Pupation inhibition and larvicidal activity of tyrosinase on Culex pipiens third-instar larvae - halaby, Hatem A. S (2023)
Mosquitoes are considered to be the main vector of a variety of diseases in both humans and domesticated animals. The development of insecticide resistance and the limitations of traditional insecticide-based strategies have resulted in significant efforts to develop eco-friendly, alternative methods.